Kompresi Adaptif untuk Streaming Multimedia Multi-Platform: A Review - Ekawati, Nia; Tresnawati, Shandy; Hanief, Shofwan; Saputro, Wahju Tjahjo (INTEK : Jurnal Informatika dan Teknologi Informasi, 2025)
The current digital era is characterized by cross-platform multimedia consumption, which has become the backbone of information and entertainment, with video content dominating more than 82% of total global internet traffic. The main challenge of adaptive compression for multi-platform multimedia streaming lies in device heterogeneity, network conditions, and the need for Quality of Experience (QoE), as adaptive compression adjusts the bitrate, resolution, and encoding level in real-time. The aim of this research is to explore these issues through a literature review study to identify the scope, taxonomy, gaps, and proposed future research directions. The method used is a literature review covering 51 publications (interval 2019-2025) to examine conceptual aspects, system taxonomy (System Architecture Layer, Adaptation Strategy, Compression Technique, and Artificial Intelligence Model), and to identify research gaps. The review results show that streaming efficiency depends on adaptive compression mechanisms, with a research paradigm shifting from rule-based adaptation toward intelligent adaptive compression. Despite these developments, significant unaddressed gaps remain, particularly concerning synchronization across platforms based on different codecs, low-latency real-time AI compression, robust network adaptation solutions for 5G/B5G, and cross-dimensional integration within a single framework. Future research directions are proposed in platform-specific synchronization models, multi-constraint compression, adaptive AI for slicing, and energy optimization through Federated Learning.